Supply Chain Performance of Cayenne Pepper in Gorontalo, Indonesia - Ria Indriani; Rahim Darma; Yunus Musa; N. Tenriawaru; Mahyuddin Mahyuddin (International Journal of Supply Chain Management, 2019)
The fluctuating price of cayenne pepper can be caused by the characteristics of agricultural commodities and also inefficient supply chain management arrangements. The research objective was to examine the performance of the cayenne supply chain with the approach of SCOR supply chain performance attributes based on reliability, responsiveness, agility, and assets in Gorontalo. The research method used was a survey method using purposive sampling technique. The study was conducted a year (July 2017-July 2018) in Gorontalo Province. Data were obtained from direct interviews with farmers, collectors, wholesalers, retailers. Data analysis utilized DEA (Data Envelopment Analysis). The results showed that the performance of the cayenne supply chain doer in Gorontalo was mostly efficient, only 5 farmers, 1 collecting trader, 1 large trader and 2 retailers whose performance was not efficient.